Marfan syndrome affecting four generations of a family without ocular involvement. Issue 788 (June 1991) - Bridges, A. B.; Faed, M.; Boxer, M.; Haining, W. M.; Pringle, T. H.; McNeill, G. P.
Abstract : Thirty eight relatives of a patient with Marfan syndrome were screened for the presence of this disorder. Marfan syndrome was newly diagnosed in living members of 4 generations in this family without evidence of ocular abnormality in any. After screening, 10 relatives were newly diagnosed as having definite, and 5 relatives as having possible, Marfan syndrome. Family screening has drawbacks as well as benefits for the patients. The main benefit is the identification and treatment of previously undiagnosed patients at risk of cardiac complications which are the major cause of mortality. The drawbacks include employment problems created for patients with Marfan syndrome as a direct consequence of our screening programme and the anxiety induced in previously asymptomatic family members who did not realize that they could be at risk. Also, the 4 adult patients with possible Marfan syndrome found it difficult to accept that a definite diagnosis could not be reached after they had been invited to attend a screening programme for a serious genetic disorder. This report illustrates the importance of screening all the relatives of a patient with Marfan syndrome to identify previously undiagnosed cases. However, before screening a family, the physician should be aware that a clear diagnosis may not be reached in all patients, and financial, psychological or social problems may arise as a result of the screening programme.